(untitled) (GAIMS Journal of Medical Sciences, 2025)
Background: Neonates with very low birth weight (VLBW) and extremely low birth weight (ELBW) has a much higher chance of experiencing serious health complications or even death. Their results depend on a myriad of newborn and maternal variables. Thus, it is important to assess and treat them specifically. Objective: The goals of this study are to quantify and assess the clinical profile, and to identify factors that are predictive of adverse outcomes of VLBW and ELBW neonates. Methods: This prospective observational research was conducted in the tertiary level neonatal intensive care unit (NICU) from 2022 to 2024. Of the 88 newborns enrolled, information gathered include factors such as birth weight, gestational age, gender, family medical history, prenatal treatment, delivery specifics, clinical trajectory and outcomes. Neonates were treated according to standard treatment guidelines. Results: There was a frequency of 1.10% for VLBW and 0.18% for ELBW. Thrombocytopenia, respiratory distress syndrome, and sepsis were among the most common complications. Results improved when antenatal steroids were used and when ANC visits were sufficient. Comparing ELBW and VLBW infants, the mortality rate was greater in the former (52.94% vs. 23.94%). Low gestational age, pulmonary hemorrhage, DIC, thrombocytopenia, and the requirement for ventilatory support were major indicators of poor prognosis. Conclusion: Neonates born with very low birth weight (VLBW) or extremely low birth weight (ELBW) are at increased risk and should receive intensive prenatal care, the early detection of maternal risk factors, and specialized newborn care. Neonatal intensive care units need to identify factors that can lead to a bad result so that they can allocate resources more wisely and intervene quickly.